Organizational Supports as Moderation in Increasing the Effect of Professionalism on Patient Safety Culture - Naufal Fakhri Nugraha; Hadi Susiarno; Hendrati Dwi Mulyaningsih (Research Synergy Foundation, 2021)
Patient safety is a fundamental concept in providing health services and it is critical that health care facilities consider it. Negligence in the application of patient safety will lead to patient safety incidents. The individual factors of medical staff have a significant influence on the implementation of patient safety. The attitude of medical staff can affect the culture of patient safety because being unprofessional will cause problems in providing quality care, encourage bad events and medical errors, and ultimately reduce patient satisfaction. Organizational support also has a role in the attitude and behavior of medical staff. There are already policies in the form of regulations from the Minister of Health, standard operating procedures, and training for medical staff. However, there are still many patient safety incidents that occurred. There is also medical staff who are not aware of the importance of reporting so that patient safety incidents are not recorded. The study was conducted in 12 Primary Health Care (PHC) in Kuningan Regency. The research method used is quantitative analysis with a cross-sectional design using a questionnaire. The research data was taken using proportional stratified random sampling to 200 medical staff in 12 PHC in Kuningan Regency. The questionnaire consists of 3 parts regarding professionalism, patient safety culture, and organizational support. The results showed that professionalism had a positive and significant impact on patient safety culture (p-value <0.001), and Organizational support is a quasi-moderating variable on the effect of professionalism on patient safety culture (p-value <0.001).